Implementation of International Standards of Fiscal and Monetary Transparency - Case of Poland - Maria JASTRZĘBSKA (Communications of International Proceedings, 2021)
Research background: Financial managers, investors, lenders, counterparties and citizens should have useful, reliable, timely, complete, comparable, readable information on fiscal and monetary policy. The actions taken and instruments used by fiscal and monetary authorities have an important impact on economic conditions. Purpose of the article: The aim of the article is to assess Poland's compliance with international standards of fiscal transparency and central bank transparency. Research methods: qualitative and descriptive analysis and inductive, deductive reasoning were applied. Findings: Raising the level of fiscal and monetary transparency is supported by compliance with international standards. In Poland, the level of monetary transparency is higher than that of fiscal transparency, with a lack of transparent information about the effects of unconventional state financial policy instruments on the economy and society.
Keywords: Transparency; Fiscal Policy; Monetary Policy